Mathematics Learning To Use Moodle-Based Hybrid Learning in SMA Negeri 1 Tembilahan Hulu - Mas`'ud Zein; Zukifli M Nuh; Dardin; Musa Thahir (Journal of Research on Mathematics Instruction (JRMI), 2019)
The development of science and technology needs to be accompanied by an increase in the quality of human resources, including through education. Education is closely related to the learning process so that one way to improve the quality of human resources is by choosing a learning model that involves technology during the learning process. One learning model that uses technology during the learning process is the Moodle-based Hybrid Learning model. The use of the Moodle-based Hybrid Learning model can help students understand the subject matter. Cognitive aspects are one important component that must be owned by students but these aspects are still relatively low. Therefore, the purpose of this article is to: 1) describe student activities during the implementation of the Moodle-based Hybrid Learning model in mathematics learning; and 2) determine the effect of Moodle-based Hybrid Learning models on student mathematics learning outcomes. This type of research is a quantitative research with experimental methods in the form of pure experimental types carried out at SMAN Negeri 1 Tembilahan Hulu with a sample size of 33 experimental classes and 33 control classes. The data collection method used in this study is a test technique. Based on the results of the analysis it can be concluded: 1) the implementation of the Moodle-based Hybrid Learning model is classified as good as seen from the mean values ​​of the experimental class 19.97 while the mean control class is 17.52; and 2) there is an influence of Moodle-based Hybrid Learning models on student mathematics learning outcomes.